Respuesta :

The solution of the equation are [tex]x = \frac{7 + \sqrt{61}}{6}[/tex] and [tex]x = \frac{7 - \sqrt{61}}{6}[/tex]

How to determine the solution?

The equation is given as:

3x^2 - 7x- 1 = 0

The quadratic equation is represented as:

[tex]x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}[/tex]

So, we have:

[tex]x = \frac{7 \pm \sqrt{(-7)^2 - 4 *3 *-1}}{2*3}[/tex]

Evaluate the expression

[tex]x = \frac{7 \pm \sqrt{61}}{6}[/tex]

Expand

[tex]x = \frac{7 + \sqrt{61}}{6}[/tex] and [tex]x = \frac{7 - \sqrt{61}}{6}[/tex]

Hence, the solution of the equation are [tex]x = \frac{7 + \sqrt{61}}{6}[/tex] and [tex]x = \frac{7 - \sqrt{61}}{6}[/tex]

Read more about quadratic formula at:

https://brainly.com/question/1214333

#SPJ1

ACCESS MORE